CONVENTIONAL THERAPY OF PSORIATIC ARTHRITIS: EVIDENCE-BASED REVIEW - E.R. Soriano; N.J. Mchugh (PAGEPress Publications, 2011)
Psoriatic arthritis is a heterogeneous condition, the pattern of which is determined by any combination of pathology affecting peripheral joints, the enthesis and the spine. There is a paucity of evidence for most of the conventional agents used to treat psoriatic arthritis, with many of them being used on the basis of experience in rheumatoid arthritis. Herein, we summarise the evidence compiled relating to effectiveness of treatment for various manifestation of PsA. For those patients with progressive forms of arthritis who may benefit from intervention of newer biological therapies, the continued use of conventional therapy needs ever increasing scrutiny. Key words: Psoriatic arthritis, psoriasis, therapy